Climate refugia for Buchanania cochinchinensis (Lour.) M.R.Almeida, an important non-timber forest tree species, declining from its natural range in India. Issue 2 (3rd April 2023) - Rajkumar, Muthu; Bhat, Poorna; Mohammad, Naseer; Ravikanth, Gudasalamani; Khan, Mohammed Latif
ABSTRACT: Buchanania cochinchinensis, a socio-economically important forest tree species, faces high levels of exploitation. Originated from the Indian subcontinent, little is known about the patterns of the habitat distribution and the important climatic factors that shape its suitability. Using high-resolution environmental data for current and future climate scenarios, we studied the present and the future suitable habitats for B. cochinchinensis by MaxEnt. We evaluated the important bioclimatic variables that shape its distribution and identified distribution shifts under different climate change scenarios. Precipitation of wettest quarter, precipitation seasonality and altitude were identified as the most critical factors shaping B. cochinchinensis distribution. The future projections under RCP2.6 (with low concentration of greenhouse gas emissions) indicate increase in the distribution range of the species. Under the scenario with higher concentrations of emissions (RCP8.5), the suitable habitat range of B . cochinchinensis has decreased. Our results showed that the refugia for B. cochinchinensis under climate change occur in Central India, especially Madhya Pradesh and Chhattisgarh.